PENGARUH PROFITABILITAS, STRUKTUR MODAL, KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PERIODE 2010-2015 - ACHMAD QUSAENI, DWI (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this research is to know the effect of profitability, capital structure, dividend policy, investment decision and Corporate Governance to company value. The type of research is a quantitative research research and conclusions in the form of causality by using purposive sampling method, so that obtained 30 companies that meet the criteria. The object of this research is the company that follow CGPI program 2010-2015 period. The data used are secondary data derived from the official website of Indonesia Stock Exchange (BEI), SWA magazine and investment world. The data analysis technique used multiple linear regression analysis. The results of this study indicate that dividend policy has a positive influence on firm value. While profitability, capital structure, investment decision corporate governanceI not affect the company value. Keyword: Profitability, Capital structure, Dividend Policy, Investment Decision, Corporate Governance Firm Value